Signifikasi Makna Kritisisme (Transendental) dalam Filsafat Imanuel Kant: Studi Kasus Filsafat Modern - Muhammad Luthfi Jalaludin Al-Habibi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the significance of transcendental-criticism in Immanuel Kant's philosophy as a case study of modern philosophy. This study uses a qualitative approach by applying descriptive methods. Immanuel Kant's theory of transcendental criticism is positioned as a formal object, while its material object is modern philosophical thought. The results and discussion in this study indicate that Immanuel Kant, through his thoughts on transcendental criticism, has tried to bridge the empiricism-rationalism flow in the case of modern Western philosophy. This study concludes that the significance of the transcendental-criticism meaning of Immanuel Kant's philosophy to test the ability of reason and determine its limits is an offer of ideas to overcome the conflict between rationalism and empiricism in the world of modern Western philosophy.